THE RELEVANCE BETWEEN PATTERN AND DURATION OF BREASTFEEDING AND THE INITIAL TIME OF GIVING WEANING FOOD WITH THE NUTRITIONAL STATUS OF TODDLER UNDER TWO IN LEMBOR VILLAGE, BRONDONG, LAMONGAN - Nurdiyanty, Selvia (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Breastfeeding to babies can affect the process of growth and development and the baby’s health. Breastfeeding is generally given exclusively for 6 months and continued until the baby reached the age of 2 years, accompanied by complementary foods when he was 6 months old for optimal nutritional status. Toddler nutrition status can be effect giving breastfeeding, infectious disease and food intake given to toddler. Objectives; to determine the relationship between pattern and duration of breastfeeding and initiation of complementary feeding with the nutritional status of two-year-old infants in Lembor Village, Brondong, Lamongan. Material and Method; This research is a correlational quantitative study using a cross sectional approach. This research was conducted in Lembor Village, Brondong, Lamongan. The sample of this study was mothers of toddler under two in Lembor Village with a simple random sampling technique with 50 sample. Results; the study found that the pattern of breastfeeding was related to nutritional status of toddler under two with p-value (0,01), the duration of breastfeeeding was related to nutritional status of toddler under two with p-value (0,02), and the initial time of giving weaning food was related to nutritional status with p-value (0,01). Conclusion; it was found that there was a correlation between the pattern of breastfeeding with the nutritional status of toddler under two, there was a correlation between the duration of breastfeeeding with the nutritional status of toddler under two, and there was a correlation between the initial time of giving weaning food with the nutritional status of toddler under two in Lembor Village, Brondong, Lamongan..